Analisis Hubungan Kuantitatif Struktur Dan Aktivitas Senyawa Turunan Triazolopiperazin Amida Menggunakan Metode Semiempirik AM1 - Anjar Purba Asmara; Mudasir Mudasir; Dwi Siswanta (Elkawnie, 2015)
QSAR studies had done on derivatives of triazolopiperazine amide as inhibitors DPP IV enzyme that causes diabetes mellitus type 2. The studies had began by modeling the structures of the derivatives of triazolopiperazine amide and calcutating the descriptors of QSAR by semiempirical AM1 method which available on HyperchemÒprogram. QSAR analysis had done by multilinear regression method analysis which is available on SPSSÒprogram using electronic and molecular parameters. The best QSAR equation model for method of semiempirical AM1:-log IC50 =  152.252 + (18,.295*qC1) + (2.343*qC5) + (2263.448*qC9) +  (1662.252*qC10) – (350.806*qC15) + (639.687*qO25)+ (6.515*EH)n = 18; r2 = 0.712; adjusted r2 = 0.510; Fhit/Ftab = 1.124; PRESS = 0.006 The main side of the compound can be determined through the equation. It can be used to study in preventing the disease of DM2 by inhibiting of enzyme DPP IV.